A QUALITY IMPROVEMENT PROJECT TO REDUCE THE USE OF COMBINATION OPIOID/ACETAMINOPHEN MEDICATIONS WITHIN A LARGE HEALTH SYSTEM. Issue 4 (28th April 2020) - Trivedi, Sunny; Shea, Kevin; Chadwick, Whitney; Gaskari, Shabnam; Wang, Ellen; Caruso, Thomas
Background: Combination analgesics are among the most commonly prescribed pain medications in pediatric orthopedic patients. However, combined analgesics do not allow for individual medication titration, which can increase the risk of opioid misuse and hepatoxicity from acetaminophen. Increasingly, the risks of combined analgesics associated with opioid misuse and hepatotoxicity are recognized by the FDA and other organizations. Given these risks, consideration should be made for independent administration of acetaminophen and opioids. Hypothesis/Purpose: The primary aim was to alter the prescribing habits of pediatric orthopedic providers at our institution from postoperative combined opioid/acetaminophen medicines to independent opioids and acetaminophen. Methods: The study took place at a children's hospital level one trauma center. A multidisciplinary team of health professionals utilized lean methodology to develop a project plan. Guided by a key driver diagram, (1) combination oxycodone/acetaminophen products were removed from hospital formulary, (2) a revised inpatient and outpatient electronic order set was implemented, and (3) multiple education efforts (emails, in person meetings) were conducted. Outcomes included inpatient and outpatient percent combined opioid/acetaminophen orders by surgical providers over twenty-seven months. Statistical process control charts were used to measure combination opioid prescribing practices for orthopedic and other surgical specialties. Results: Prior to intervention, inpatient combination opioid/acetaminophen products were prescribed for an average of 46% of all opioid prescriptions for orthopedic patients. After intervention and multiple educational efforts, the percent of combined opioid/acetaminophen products dropped to 31% and then to 3% by end of the investigational period. For outpatient prescriptions, the combined products accounted for 88% prior to intervention and dropped to 15% at project completion. Conclusion: By removing combined oxycodone/acetaminophen products from hospital formulary, educating the medical staff, and employing electronic order sets, the inpatient/outpatient prescribing practice of pediatric orthopedic surgeons changed from the common use of combined opioid/acetaminophen products to independent medications. This project demonstrates that changing medication prescription practice can be accomplished with 3 steps within a hospital system. Reducing the use of combination opioid/acetaminophen products may have further positive impacts on opioid misuse and hepatoxicity.